Ordering Uncertain Options under Inflation: A Note - LEVY, HAIM; LEVY, AZRIEL (Journal of Finance, 1984)
ABSTRACT Stochastic dominance rules (SD) have been extended to the case where investors are allowed to borrow and lend at the riskless interest rate. Stochastic dominance rules with a riskless asset (SDR) are much more effective than SD rules. However, it seems that this benefit is eliminated by an uncertain inflation, since riskless assets become risky once uncertain inflation is considered. We prove in this paper that SDR criteria are valid also in the face of uncertain (and independent) inflation. Moreover, while the mean‐variance (MV) efficient set increases with uncertain inflation, the stochastic dominance efficient sets decrease.